Pemberdayaan UMKM Warung Nasi Bu Menik Melalui Pemasaran Digital di Desa Keboananom Sidoarjo - Anisa Putri Anjani; Virginia Mandasari (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The Warung Nasi Bu Menik MSME in Keboananom Village faces the challenge of limited marketing reach, which hinders the growth of its consumer base. This community service project aims to increase the visibility and accessibility of the business by optimizing the Google Maps platform and Facebook social media. The method used is participatory assistance, which includes adding the business location to Google Maps and creating and managing promotional content on the Facebook account. The results of the activity show that the integration of Google Maps has succeeded in facilitating consumer navigation to the physical location, while the use of Facebook has significantly expanded product information exposure. The use of integrated digital media has proven to be effective in increasing the online presence of MSMEs, which is a crucial foundation for the competitiveness of micro businesses in the digital era.